THE POTENTIAL OF EXPERT SYSTEMS IN FACILITIES PLANNING - Perlmann, Avron Michael; Bailey, Martin (The South African Journal of Industrial Engineering, 2011)
This paper discusses the use of "nan traditional" techniques for solving facilities planning problems. especially where a large amount of heuristic data must be analysed. The application of expert systems in optimizing the planning of facilities and other computer based models are discussed and evaluated in order to determine the effectiveness of these systems. The future of expert logistic problems and are determined. The short. medium and long term application of expert systems as well as a case study of a system presently being used for facilities design are discussed. The integration of an expert system with/simulation and design modelling techniques is investigated.